Milk sample testing portal - Van Campenhout, Bjorn (CGIAR, 2023)
As part of a research project to improve the quality of milk in dairy value chains in Uganda, researchers from the CGIAR Rethinking Food Markets Initiative together with the Dairy Development Authority installed about 75 milk analyzers in randomly selected Milk Collection Centers in Mbarabra, Kirihura, Kazoo and Ntungamo. These milk analyzers allow milk collection centers to test incoming milk from farmers on a range of important quality markers, such as butter fat content, solids non-fat (SNF), protein, added water, etc in a matter of seconds using a small sample of milk. We also provided the milk collection centers with a tablet computer and a custom application designed to enter the data from the milk analyzers, making it easier to track quality.